2017
DOI: 10.1089/acm.2016.0236
|View full text |Cite
|
Sign up to set email alerts
|

Providers' and Administrators' Perceptions of Complementary and Integrative Health Practices Across the Veterans Health Administration

Abstract: Objectives: Use of complementary and integrative health (CIH) therapies is being promoted by the Veterans Health Administration (VA), but promotion may not equate to adoption. The purpose of this study was to explore whether perceptions regarding CIH at one VA medical center (VAMC) were similar to perceptions from a sample of other VAMCs.Design: This article reports a subset of qualitative findings from a mixed-methods study. Setting/Participants: Sites were recruited through a VA-wide CIH listserver. On the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…These common complaints are consistent with already identified barriers to treatments within the scientific literature. 47,54,55,57,58,7274…”
Section: Discussionmentioning
confidence: 99%
“…These common complaints are consistent with already identified barriers to treatments within the scientific literature. 47,54,55,57,58,7274…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, perhaps the disadvantages of Western medicine in the treatment of chronic diseases have fuelled health care professionals’ optimism about TCM [ 19 ]. According to patients, CAM may not only cure [ 20 ] but also may counterbalance the adverse effects of Western medicine [ 21 23 ], improve physical and mental health, promote positive medical outcomes and wellness [ 24 – 27 ], etc. TCM may also enhance the comprehensive outcomes of preventive and treatment efforts and heighten the effectiveness of health interventions and assessments [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Healthcare leaders' support for CIH therapies is instrumental for successful implementation. [28][29][30][31][32] However, little is known about how to garner such support and what motivates leaders' provision or withholding of support. In two prior studies, leaders identified individual knowledge/ attitudes toward CIH, perceptions of patients, traditional medical culture, champions, and organizational issues as barriers or facilitators to CIH implementation.…”
Section: Introductionmentioning
confidence: 99%
“…In two prior studies, leaders identified individual knowledge/ attitudes toward CIH, perceptions of patients, traditional medical culture, champions, and organizational issues as barriers or facilitators to CIH implementation. 28,32 Yet how these barriers/facilitators may influence leaders' decisionmaking has not been fully explored. Therefore, we sought to examine leaders' reasons for providing or withholding concrete support for CIH in early adopting VAMCs.…”
Section: Introductionmentioning
confidence: 99%